Increasing parental self-efficacy with emotion-focused family therapy for eating disorders: a process model. (3rd July 2017) - Strahan, Erin J.; Stillar, Amanda; Files, Natasha; Nash, Patricia; Scarborough, Jennifer; Connors, Laura; Gusella, Joanne; Henderson, Katherine; Mayman, Shari; Marchand, Patricia; Orr, Emily S.; Dolhanty, Joanne; et al.
ABSTRACT: A process model was tested whereby parental fear and self-blame were targeted in order to enhance parental self-efficacy and supportive efforts in the context of emotion-focused family therapy (EFFT) for eating disorders (ED). A 2-day EFFT group intervention was delivered to parents of adolescent and adult children with ED. Data were collected from eight treatment sites ( N = 124). Data were analyzed using t -tests, regression analyses and structural equation modeling. The findings supported the proposed process model. Through the processing of parents' maladaptive fear and self-blame, parents felt more empowered to support their child's recovery. This increase in self-efficacy led to an increase in parents' intentions to engage in recovery-focused behaviors. This study is the first to test a method for clinicians to increase supportive efforts by targeting and enhancing caregiver self-efficacy via the processing of emotion.